Desenvolvimento de um portal educativo para o programa de educação permanente de um hospital público no sul do país - Fontana, Eva Joseane (Universidade do Vale do Rio dos Sinos, 2020)
The Permanent health education has been considered as an instrument to produce changes and transformations in professional performances and working contexts, involving information technologies and communication (ITC) technologies as mediators in this process. Besides being facilitator and multipliers in teaching, the information technologies (ITs) provides autonomy and responsibility for the acquisition of knowledge itself, contributing and positively transforming the processes of the Unified Health System (SUS). OBJECTIVE: To develop an educational portal for the Permanent Education Program (PEP) in the intranet of a public hospital in southern Brazil. METHOD: Methodological study involving three stages: documentary research, construction and validation of the educational portal. The documentary research was based on the model adapted according to Cellard. The construction of the educational portal used the DADI method and the validation followed the recommendations of the ISO / IEC 25010 standard and the evaluation process defined in standard 14598-6. For content evaluation, the Instrument for validating educational content in health (IVCES) was used. RESULTS: The documentary research allowed to know the strategies used for the implementation of the PEP, to identify the actions of integration and teaching in service developed in the institution and also made it possible to raise the needs for the construction of the educational portal. The evaluation and validation process of the the educational portal involved three groups: IT staff, specialists represented by the leaders of the nursing and medical areas and by nursing assistants and nursing technicians. The assessment carried out by the IT team, showed 100% positive responses in the categories of efficiency, functionality, usability and compatibility. Maintainability showed 62.5% agreement. In the experts' evaluation, the educational portal obtained 100% of the positive responses in the categories of efficiency, usability and functionality. The assistance team composed of nurses and nursing technicians validated the content obtaining 82% of agreement, on the items related to the objectives 80% of agreement and 84% of agreement in the evaluation of the structure / presentation. Conclusion: It is concluded that the Portal stood out in four characteristics: efficiency, functionality, usability and compatibility and in the content evaluation, being considered apt as a product. This research, which had as product the production of an educational portal, will assist in the institutional communication and in the permanent education activities, as well as in process improvement and in the quality of nursing care and other areas of the institution.
Keywords: Educação permanente; Website; Enfermagem; Hospital; Permanent education; Web site; Nursing; ACCNPQ::Ciências da Saúde::Enfermagem